Global Responses to Rural Challenges: Exploring Rural Education in Trinidad and Tobago - Alicia Noreiga-Mundaroy (Canadian Society for Studies in Education, 2021)
Trinidad and Tobago has been unsuccessful in evading global trends of neglect that historically plague the country's rural education. This paper employs theoretical perspectives developed internationally to provide comprehensive insights into rural education challenges in Trinidad and Tobago. This critical review systematically highlights rural controversies by exploring conceptual underpinnings that place rural Trinidad and Tobago in a unique position within a continually evolving global space. The arguments put forward in this literature review analyze the challenges of the country's rural communities and promote rural schools as functional in address rural community challenges while noting the challenges that these very schools are confronted with daily. The paper offers initial steps to tackle the challenges of the schools as a basis to empower them to create an opportunity for meaningful discourse toward addressing not only Trinidad and Tobago's challenges, but also rural challenges globally.